Starved and Asphyxiated: How Can CD8+ T Cells within a Tumor Microenvironment Prevent Tumor Progression - Zhang, Ying; Ertl, Hildegund C. J. (Frontiers in Immunology, 2016)
Although cancer immunotherapy has achieved significant breakthroughs in recent years, its overall efficacy remains limited in the majority of patients. One major barrier is exhaustion of tumor antigen (TA)-specific CD8+ tumor-infiltrating lymphocytes (TILs), which conventionally has been attributed to persistent stimulation with antigen within the tumor microenvironment (TME). A series of recent studies have highlighted that the TME poses significant metabolic challenges to TILs, which may contribute to their functional exhaustion. Hypoxia increases the expression of co-inhibitors on activated CD8+T cells, which in general reduces the T cells’ effector functions. It also impairs the cells’ ability to gain energy through oxidative phosphorylation (OXPHOS). Glucose limitation increases expression of programmed cell death protein (PD)-1 and reduces functions of activated CD8+T cells. A combination of hypoxia and hypoglycemia, as is common in solid tumors, places CD8+TILs at dual metabolic jeopardy by affecting both major pathways of energy production. Recently, a number of studies addressed the effects of metabolic stress on modulating CD8+T cell metabolism, differentiation and functions. Here we discuss recent findings on how different types of metabolic stress within the TME shape the tumor-killing capacity of CD8+T cells. We propose that manipulating the metabolism of TILs to more efficiently utilize nutrients especially during intermittent periods of hypoxia could maximize their performance, prolong their survival and improve the efficacy of active cancer immunotherapy.